2020
DOI: 10.1103/physrevd.101.124005
|View full text |Cite
|
Sign up to set email alerts
|

NUT charge in linearized infinite derivative gravity

Abstract: We study the gravitational field of the NUT-like source in the linearized (ghost-free) infinite derivative gravity. Such a source is equivalent to the spinning semi-infinite cosmic string with no tension. In general relativity, the linearized (massless) Taub-NUT solution has a curvature singularity as well as a topological defect corresponding to distributional curvature on one half of the symmetry axis called the Misner string. We find the NUT-charged spacetime in the linearized infinite derivative gravity. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 65 publications
(103 reference statements)
3
38
0
Order By: Relevance
“…At the classical level, it has been shown that the linearized IDG can yield nonsingular static solutions for point sources (including electromagnetic charges), p-branes (and cosmic strings), sources describing Newman-Unti-Tamburino charges [27,[38][39][40][41], and spinning ring distributions [42]. It was also found that the linearized IDG prevents mini-black-hole production for small masses [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…At the classical level, it has been shown that the linearized IDG can yield nonsingular static solutions for point sources (including electromagnetic charges), p-branes (and cosmic strings), sources describing Newman-Unti-Tamburino charges [27,[38][39][40][41], and spinning ring distributions [42]. It was also found that the linearized IDG prevents mini-black-hole production for small masses [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been further progress in finding solutions of linearized IDG. It was shown that IDG may avoid not only black-hole type singularities [26][27][28][29][30][31][32][33], but also topological defects such as p branes [34], cosmic strings [35], and NUT-like singularities [36]. The exact pp-wave solutions have been studied in [37].…”
Section: Introductionmentioning
confidence: 99%
“…The solution of Eq. ( 21) can be found analytically in the case of N ¼ 1 [52]. Here we rewrite it in terms of the smeared δ-function and Heaviside function as follows:…”
Section: Nut Solutionmentioning
confidence: 99%
“…The NUT solution for weak-field nonlocal gravity has been constructed via Laplace transform methods in Ref. [52]. Here we would like to briefly delineate a possibly simpler derivation of the NUT solution that simultaneously extends to more general nonlocal theories of the GF N type.…”
Section: Appendix: Derivation Of the Nut Solutionmentioning
confidence: 99%
See 1 more Smart Citation